Analysıs of Emotıonal Intellıgence and Personalıty Traıts of Students In Faculty of Sports Scıences - Balyan, Melih (2021)
This study it was aimed to examine the emotional intelligence and personality traits of the students who study in different departments of the Faculty of Sport Sciences at Ege University and actively do sports in different sports branches.  In total 549 students participated in the study voluntarily. To evaluate the variables of the study, the Schutte Emotional Intelligence Scale developed by Schutte et al. (1998) and adapted into Turkish by Tatar et al. (2011), and to evaluate personality traits, five-factor personality inventory developed by Somer, Tatar, and Korkmaz (2004) and whose short form was validated and reliable by Tatar (2005) were used. In this study, the data set was SPSS 22.0, and it was completed by using frequency tables, reliability analysis, independent sample t-test, one-way variance analysis, Tukey test, and correlation analysis in analyzes. There is both a significant (p<0.05) and an insignificant (p>0.05) difference between emotional intelligence and subscales of personality according to the department, type of education, average grade, class, gender, age and branches. There is no significant difference between emotional intelligence and personality (p> 0.05). They are independent of each other. As a result, as the concepts of emotional intelligence and personality affect individuals deeply, the main purpose of this study is to find the necessary information with the necessary studies to better understand the students in the sports science faculty. This study is to measure the emotional intelligence and personality traits of the students studying at the Faculty of Sport Sciences at Ege University and to examine the relationship between emotional intelligence and personality. We think that it is an important study as it will make a serious contribution to the studies by repeating similar studies and applying them to large sample groups in different fields in different universities and different branches.